Observation of Excitonic Fine Structure in a 2D Transition-Metal Dichalcogenide Semiconductor - Shang, Jingzhi; Shen, Xiaonan; Cong, Chunxiao; Peimyoo, Namphung; Cao, Bingchen; Eginligil, Mustafa; Yu, Ting (ACS nano, 2015)
Two-dimensional (2D) semiconductors, such as transition-metal dichalcogenide monolayers (TMD 1Ls), have attracted increasing attention owing to the underlying fundamental physics (e.g., many body effects) and the promising optoelectronic applications such as light-emitting diodes. Though much progress has been made, intrinsic excitonic states of TMD 1Ls are still highly debated in theory, which thirsts for direct experimental determination. Here, we report unconventional emission and excitonic fine structure in 1L WS2 revealed by electrical doping and photoexcitation, which reflects the interplay of exciton, trion, and other excitonic states. Tunable excitonic emission has been realized in a controllable manner via electrical and/or optical injection of charge carriers. Remarkably enough, the superlinear (i.e., quadratic) emission is unambiguously observed which is attributed to biexciton states, indicating the strong Coulomb interactions in such a 2D material. In a nearly neutral 1L WS2, trions and biexcitons possess large binding energies of ∼10–15 and 45 meV, respectively. Moreover, our finding of electrically induced robust emission opens up a possibility to boost the luminous efficiency of emerging 1L TMD light emitting diodes.